Basic Principles of Longevity of Life In Ayurveda- A Review - Bijarniya, Sunita Kumari; Kapoor, Ritu; Upadhyay, Parmanand (International Research Journal of Ayurveda & Yoga, 2020)
Longevity in Ayurvedic terms is Deerghaau. At present time, it is a strong issue because day by day increasing pollution and unhealthy lifestyle are decreasing the average age of a human.In Ayurveda, Aachaaryaas have enlightened many principles of Deerghaau like- ritu parichariyaa and shodasha sanskaraas (beejdharana, garbhadharana etc). Aachaaryaas have also mentioned the drugs in each decade (10 yrs.) of life for desirable effects (like bala, buddhi etc.). For long and healthy life our Aachaaryaas have emphasised on aahar- vihar . according to kaala satmya (seasonal adaptability), Desh satmya( climate and place adaptability), Prakriti satmya(person to person adaptability) etc. If not follow these principles one can suffer from many diseases and this may lead to unnatural death that is known as akaala mrtyu. Akaala mrtyu is unnatural progressive death of cells and tissues. It can stopped by akaala mrtyu samprapti vighatana and rejuvenising the decaying body through ayurvedic procedures like- sodhana karma, rasayana prayoog, snehan karma which further promotes the oja in the body.